2005
DOI: 10.1039/b417905f
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-evolving Photosystem II core complexes: a new paradigm based on the spectral identification of the charge-separating state, the primary acceptor and assignment of low-temperature fluorescence

Abstract: We review our recent low-temperature absorption, circular dichroism (CD), magnetic CD (MCD), fluorescence and laser-selective measurements of oxygen-evolving Photosystem II (PSII) core complexes and their constituent CP 4 3, CP 47 and D1/D2/cytb(559) sub-assemblies. Quantitative comparisons reveal that neither absorption nor fluorescence spectra of core complexes are simple additive combinations of the spectra of the sub-assemblies. The absorption spectrum of the D1/D2/cytb(559) component embedded within the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
60
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 62 publications
27
60
0
Order By: Relevance
“…However, Krausz, et al (2005) found that there is charge separation in PS II in spinach even over the range 700-730 nm. So, uphill energy transfer is not the most productive way to obtain energy, but nonetheless the phenomenon indicates more means of light harvesting, while resonance transfer of energy toward the red is the dominant means of light harvesting and energy trapping.…”
Section: Pigment Absorbance Energeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Krausz, et al (2005) found that there is charge separation in PS II in spinach even over the range 700-730 nm. So, uphill energy transfer is not the most productive way to obtain energy, but nonetheless the phenomenon indicates more means of light harvesting, while resonance transfer of energy toward the red is the dominant means of light harvesting and energy trapping.…”
Section: Pigment Absorbance Energeticsmentioning
confidence: 99%
“…Also, the Chl a primary donor of PS I has its peak absorbance at 700 nm. Significant phenomena occur in the red edge region (Krausz, et al, 2005, called it "spectral congestion" with regard to an even more detailed structural antenna minor sub-bands occur for PS I and PS II; 678.5 nm, the main sub-band for PS II; 680 nm, the location of the primary donor P680 for PS II; 682 nm, the main sub-band for PS I; and 700 nm, the primary donor P700 for PS I. The main sub-bands are actually where most of the light harvesting of the core antenna occurs.…”
Section: Pigment Absorbance Energeticsmentioning
confidence: 99%
“…It was possible to establish not only the presence of these carotenes but even their orientations because of the improvement in the structural X-ray method. Nevertheless, Krausz et al (2005) did not show the presence of these Cars. Cars in the organisms can play three roles: (1) they can work as light-harvesting pigments transferring the energy absorbed to Chls: 1 Car + hν → 1 Car * → 1 Chl * (1)…”
Section: Pigment De-excitation and Mutual Interactionsmentioning
confidence: 59%
“…The mechanism responsible for their role in prevention of the damage to PS2 RC by too strong irradiation was discussed taking into account the actual distances between pigment molecules obtained in experiments (Telfer 2005). The data concerning PS2 core complexes in which the presence of these carotenes was not taken into account were recently published (Krausz et al 2005). Telfer (2005) added that one of the two β-carotenes located near PS2 RC in PS2 core structure, bound to D2 complex, is more or less parallel to the plane of membrane, whereas the other one is roughly perpendicular to the membrane plane.…”
Section: Pigment De-excitation and Mutual Interactionsmentioning
confidence: 99%
“…[11] However, even with its great success, some electron transfer problems have struggled to reach a consensus through advancements of the Marcus Theory framework. Our favourite example is the primary photo-energetics of charge separation Photosystem II where difficulty arises in physically explaining the ultrafast kinetics and energy-trapping events, [12][13][14] not to mention the catalytic four-electron water oxidation chemistry. [15,16] This example also highlights our theme, the chemical problem of energy change.…”
Section: We Understand Single-electron Transfer Processesmentioning
confidence: 99%